Artificial Intelligence, IoT, and Digital Literacy for Sustainable Farming and Hunger Mitigation - Anirudh Edupuganti (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The growing challenges of climate change, food insecurity, and the digital divide have motivated significant research into artificial intelligence (AI), the Internet of Things (IoT), and digital education as enablers of sustainable farming. This review synthesizes multiple internationally recognized papers published between 2015 and 2024, covering three thematic domains: AI and IoT applications in farming, AI-powered education and digital literacy for rural communities, and farming’s role in hunger mitigation within the framework of Sustainable Development Goal 2 (Zero Hunger). It was found that AI and IoT innovations improve crop yield, resource efficiency, and pest management; AI-driven education platforms enhance farmers’ skills and digital inclusion; and targeted agricultural interventions can significantly reduce hunger risk. However, issues of infrastructure, affordability, digital literacy, and policy integration remain critical challenges. Future work has been suggested toward integrated frameworks combining AI, IoT, and education platforms to enable scalable, inclusive, and climate-resilient farming systems.